The Discount Rate Problem in Capital Rationing Situations: Reply - Lusztig, Peter; Schwab, Bernhard (Journal of Financial and Quantitative Analysis, 1970)
In our earlier note, we drew attention to the problem of interdependency between the opportunity cost used as a discount rate in determining the net present values of the objective function and the optimal solution of a linear program. In expanding on our article, Lockett and Tompkins (L and T) rightly point to the need for an appropriate definition of opportunity costs.